2018
DOI: 10.18410/jebmh/2018/478
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Parameters and Vitamin B12 Levels in Type Ii Diabetic Patients on Metformin- A Prospective Case Control Study

Abstract: BACKGROUND Metformin is the cornerstone medication in the management of type 2 diabetes mellitus (T2DM) with estimates that it is routinely prescribed to 120 million type 2 diabetes patients around the world. Preceding studies say long term use of metformin in T2DM lowers vitamin-B12 levels and its clinical manifestations can be misdiagnosed as diabetic peripheral neuropathy. The aim of this study is to correlate haematological parameters with estimated serum Vit. B12 levels in T2DM patients on long term metfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…This result is consistent with those reported in other studies [4,19]. In contrast, some authors have shown that the reduction of serum vitamin B 12 concentration is associated with duration of metformin therapy and is induced in a dose-dependent manner [16,18,20,38] The complex interaction between the oxidative stress and inflammation in T2DM patients contribute to the alteration of erythrocyte homeostasis and cause an increase in RDW values [1,23,26]. Vitamin B 12 possesses antioxidant properties, and subclinical vitamin B 12 deficiency may contribute to oxidative stress through various mechanisms [36].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with those reported in other studies [4,19]. In contrast, some authors have shown that the reduction of serum vitamin B 12 concentration is associated with duration of metformin therapy and is induced in a dose-dependent manner [16,18,20,38] The complex interaction between the oxidative stress and inflammation in T2DM patients contribute to the alteration of erythrocyte homeostasis and cause an increase in RDW values [1,23,26]. Vitamin B 12 possesses antioxidant properties, and subclinical vitamin B 12 deficiency may contribute to oxidative stress through various mechanisms [36].…”
Section: Resultssupporting
confidence: 93%
“…By multiple linear regression analysis, we found that older patients had statistically significantly lower serum vitamin B 12 levels. A significant negative relationship between age and vitamin B 12 level in T2DM patients using metformin for 1 -10 years was reported by Koduri et al [18]. The vitamin B 12 status depends on both the amount ingested and the proper functioning of the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 84%